2002
DOI: 10.1046/j.1365-2842.2002.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Complications and failures in removable partial dentures: a clinical evaluation

Abstract: The design of removable partial dentures (RPDs) is an important factor for good prognostication. The purpose of this study was to clarify the effectiveness of denture designs and to clarify the component that had high rates of failure and complications. A total of 91 RPDs, worn by 65 patients for 2-10 years, were assessed. Removable partial dentures were classified into four groups: telescopic dentures (TDs), ordinary clasp dentures (ODs), modified clasp dentures (MDs) and combination dentures (CDs). The failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 7 publications
1
42
1
4
Order By: Relevance
“…The retentive force decreases as the tapered angle increases, and so the suitable tapered angle of the cone crown telescopic system is reported to be 6° for type 4 gold alloys 28) . The greater height of the cone crown telescopic system increases the retentive force 29) , but the diameter of the cone crowns does not affect the retentive force 30) . The retentive force increases with thicker outer crown.…”
Section: Introductionmentioning
confidence: 97%
“…The retentive force decreases as the tapered angle increases, and so the suitable tapered angle of the cone crown telescopic system is reported to be 6° for type 4 gold alloys 28) . The greater height of the cone crown telescopic system increases the retentive force 29) , but the diameter of the cone crowns does not affect the retentive force 30) . The retentive force increases with thicker outer crown.…”
Section: Introductionmentioning
confidence: 97%
“…Double crown-retained removable dental prostheses (RDP) have been clinically proven to be a successful treatment option in the prosthetic dentistry [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The versatility and advantages of double crown retainers for RDP have recently been emphasized once again [17].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports are available on the survival of RDP, survival of abutment teeth, and complications of cast double crown-retained RDP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The current dental literature, however, does not provide sufficient information about the clinical performance of RDP retained by electroplated double crown systems.…”
Section: Introductionmentioning
confidence: 99%
“…The main problems that patients encounter after insertion of the removable dentures are loss of retention, ulcers, denture stomatitis, loss of artificial teeth, epulis fissuratum, fractured denture base etc. [4][5][6] Failure of dentures will affect oral health and in turn the quality of life. There are only few studies reported evaluating complications after treatment with removable dentures.…”
Section: Introductionmentioning
confidence: 99%